2021
DOI: 10.1002/emp2.12477
|View full text |Cite
|
Sign up to set email alerts
|

Effect of language interpretation modality on throughput and mortality for critical care patients: A retrospective observational study

Abstract: Objective Limited data exist describing possible delays in patient transfer from the emergency department (ED) as a result of language barriers and the effects of interpretation services. We described the differences in ED length of stay (LOS) before intensive care unit (ICU) arrival and mortality based on availability of telephone or in‐person interpretation services. Methods Using an ICU database from an urban academic tertiary care hospital, ED patients entering the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Data from the Australian Stroke Clinical Registry, however, showed that patients requiring interpreters had comparable discharge outcomes but poorer health-related quality of life compared to patients not requiring interpreters (Kilkenny et al, 2018). The effect of language barrier on ED length of stay has also been evaluated in non-stroke populations where critically ill, non-English speaking patients were reported to spend an average of 17-35 more minutes in the ED before arriving to ICU leading to higher mortality rates (Oca et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Data from the Australian Stroke Clinical Registry, however, showed that patients requiring interpreters had comparable discharge outcomes but poorer health-related quality of life compared to patients not requiring interpreters (Kilkenny et al, 2018). The effect of language barrier on ED length of stay has also been evaluated in non-stroke populations where critically ill, non-English speaking patients were reported to spend an average of 17-35 more minutes in the ED before arriving to ICU leading to higher mortality rates (Oca et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As for its explicit and implicit benefits, some scholars believe that the value of language essence refers to its implicit benefits, namely its importance, standardization, language history, civilization, information, recorded text data, etc. The specific expression of its application value is also a focus of scholars' attention, generally divided into language and social function [8], such as the number of uses, scope, and related benefits. Some scholars believe that "language resources have implicit and explicit benefits.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Consequently, patients with LEP face significant disparities. Hospitalized patients with LEP are at a higher risk of adverse medical events [6], have less fully documented informed consent [7], longer hospital and ICU stays [8,9], higher readmission rates [9][10][11], and increased ICU mortality rates [12]. At end of life, patients with LEP are more likely to receive mechanical ventilationand are less likely to receive a comfort measures order set [8].…”
Section: Introductionmentioning
confidence: 99%